CRIMINAL LIABILITY FOR FRAUDULENT PRACTICES IN THE SELECTION EXAMINATION FOR CIVIL SERVICE CANDIDATES (CASN) - Syahrani, Dhiva; Deni Achmad; Firganefi; Tri Andrisman (Progressive Law Review, 2025)
Cheating on the Civil Service Candidate (CASN) test is an unlawful act committed by an individual or group of individuals that can damage the integrity of the civil service selection process. This act is carried out by manipulating electronic documents in the Civil Service Candidate selection test to make it appear as if the applicant's data is authentic in order to take the test (CASN). Perpetrators may be held criminally liable, either individually or jointly, according to their role in the crime. Therefore, what form of criminal liability does cheating on the Civil Service Candidate (CASN) selection test take. This study uses a normative legal approach supported by empirical legal evidence using the applicable laws and regulations as well as literature studies and interviews with sources in this study consisting of judges at the Tanjung Karang District Court and lecturers from the Criminal Law Department of the Faculty of Law at the University of Lampung. Descriptive qualitative data analysis The results of the research and discussion show that the defendant's criminal liability for manipulating personal data in the Civil Service Candidate Selection System (SSCASN) based on Decision Number 510/Pid.Sus/2024/PN TJK is based on two main elements, namely unlawful acts and intentional mistakes. The defendant was proven legally and convincingly to have falsified the identity photos on the ID cards of selection participants for personal gain as a proxy in the CPNS test, thereby fulfilling the elements of Article 35 in conjunction with Article 51 Paragraph (1) of the ITE Law. The Panel of Judges found no justifiable or exculpatory reasons that would eliminate criminal liability and assessed that the defendant was capable of being held responsible, thus declaring him guilty and imposing a criminal penalty.